Correlation of shoulder tip pain in case of low pressure and standard pressure pneumoperitoneum post laparoscopic cholecystectomy - Agarwal, Lakshman; Kumawat, Sanjay; Jain, Sumita A.; Yadav, Amit; Sharma, Sandeep (International Surgery Journal, 2021)
Background: Laparoscopic cholecystectomy is gold standard treatment for cholelithiasis now a days. Post-operative shoulder tip pain is common complain after laparoscopic cholecystectomy. The cause of this shoulder tip pain is multifactorial e.g. peritoneal stretching and diaphragmatic irritation. The main cause of this shoulder tip pain is pneumoperitoneum caused by carbon dioxide. Correlation of shoulder tip pain in case of low pressure (7-8 mmHg) and standard pressure (12-14 mmHg) pneumoperitoneum post laparoscopic cholecystectomy. Methods: A prospective randomized study was done in 100 patients of cholelithiasis in SMS hospital Jaipur Rajasthan. The patients were divided into two groups-Group A patients undergoing laparoscopic cholecystectomy at low pressure (7-8 mmHg) and group B patients undergoing laparoscopic cholecystectomy at standard pressure (12-14 mmHg). The intensity of shoulder tip pain were measured by visual analogue score at 1, 6, 12, 24 and 48 hours. In both of the group results were compared in terms of frequency of pain, intensity of pain and requirement of post-operative analgesics. The duration of hospital stay was also compared. Results: Post-operative shoulder tip was found to be less in low pressure group (group A) as compare to standard pressure group (group B). Total requirement of post-operative analgesic dose and hospital stay was also found to be less in low pressure group as compared to standard pressure group. This was statistically significant (p value<0.05). Conclusions: There is less intensity, frequency of shoulder tip pain, less post-operative analgesics requirement and less post-operative hospital stay after laparoscopic cholecystectomy done under low pressure pneumoperitoneum (7-8 mmHg).